2018
DOI: 10.17350/hjse19030000097
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flocs in Dewatering of Coal Plant Tailings

Abstract: L ignite coal, which has a large share in world coal reserves, must be subjected to coal preparation processes in coal washing plants due to its low calorific value and high ash content. After these processes, the huge amount of tailings is produced from the plants, and they must be dewatered before disposal. For this purpose, flocculation is a widely preferred method for solid-liquid separation of fine coal tailings. In this method, long-chain polymers are used to bind particles together to form bigger partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The coagulation/flocculation experiments were carried out with the coal tailing sample at 5% solids ratio (w/v) at room temperature (23°C). 10 -3 , 10 -2 , 10 -1 , and 1 mol/dm 3 ion concentrations and 50, 150, and 300 g/Mg flocculant dosages were used in the light of the results of Gungoren et al (2018). The experiments were carried out at natural pH (~6.87).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coagulation/flocculation experiments were carried out with the coal tailing sample at 5% solids ratio (w/v) at room temperature (23°C). 10 -3 , 10 -2 , 10 -1 , and 1 mol/dm 3 ion concentrations and 50, 150, and 300 g/Mg flocculant dosages were used in the light of the results of Gungoren et al (2018). The experiments were carried out at natural pH (~6.87).…”
Section: Methodsmentioning
confidence: 99%
“…Duzyol (2016) used Taguchi (L16) experimental design to determine the optimum conditions for the turbidity removal from fine coal suspensions and found that the most influential factor was the polymer dosage. Therefore, the flocculant dosage should be optimized for an effective flocculation process (Gungoren et al, 2018).…”
Section: Flocculation Experiments In the Absence Of Ionsmentioning
confidence: 99%